Manufacturing strategies for highly sensitive and self-powered piezoelectric and triboelectric tactile sensors - Hyosik Park; Gerald Selasie Gbadam; Simiao Niu; Hanjun Ryu; Ju-Hyuck Lee (International Journal of Extreme Manufacturing)
Piezoelectric and triboelectric effects are of growing interest for facilitating high-sensitivity and self-powered tactile sensor applications. The working principles of piezoelectric and triboelectric nanogenerators provide strategies for enhancing output voltage signals to achieve high sensitivity. Increasing the piezoelectric constant and surface triboelectric charge density are key factors in this enhancement. Methods such as annealing processes, doping techniques, grain orientation controls, crystallinity controls, and composite structures can effectively enhance the piezoelectric constant. For increasing triboelectric output, surface plasma treatment, charge injection, microstructuring, control of dielectric constant, and structural modification are effective methods. The fabrication methods present significant opportunities in tactile sensor applications. This review article summarizes the overall piezoelectric and triboelectric fabrication processes from materials to device aspects. It highlights applications in pressure, touch, bending, texture, distance, and material recognition sensors. The conclusion section addresses challenges and research opportunities, such as limited flexibility, stretchability, decoupling from multi-stimuli, multifunctional sensors, and data processing.